Detection of Isomorphism in Planar Kinematic Chains - Kunal Dewangan (International Journal of Advanced Science and Technology, 2020)
This work manages the issue of location of isomorphism among planar kinematic chains among six link one degree of freedom, eight link one degree of freedom, nine link two degree of freedom and ten link three degree of freedom kinematic chains. This study will help the designer to avoid duplication of the kinematic chains, at the conceptual stage of design. In this approach, a path matrix (PM) is shaped utilizing the qualities based on the parameter. Isomorphism is detected on the basis of kinematic chain string (KCS) of path matrix (PM).